2012
DOI: 10.1016/j.fluid.2012.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and transport properties of CO2+N2O and CO2+NO mixtures: Molecular simulation and equation of state modelling study

Abstract: In the present study, the thermodynamic behaviour and transport properties of CO 2 +N 2 O and CO 2 +NO mixtures have been investigated using molecular simulation and equation of state modelling. Molecular simulations were based on Monte Carlo and Molecular Dynamics calculations using force fields calibrated from pure component properties and no adjustment of mixture properties was performed. Original force fields were proposed for N 2 O, NO and N 2 O 2 molecules. Special attention must be paid when studying ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 51 publications
(57 reference statements)
1
35
0
Order By: Relevance
“…[17,34] Similarly, numerical simulations are interesting tools when the considered molecules are toxic for human, which is typically the case of systems containing H 2 S. [35,36,37] In numerous studies we have reported the use of molecular simulation techniques to obtain pseudo experimental data for gas mixtures. [38,39,40,41,42,43,44] In these studies, simulated vapour-liquid equilibrium data were compared to corresponding experimental data points, and scaling laws together with additional molecular simulation results were used to calculate critical point coordinates. [39,40,42] The so obtained phase envelops can then be used to optimize binary interaction parameter values to feed EoS.…”
Section: Atomistic Molecular Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,34] Similarly, numerical simulations are interesting tools when the considered molecules are toxic for human, which is typically the case of systems containing H 2 S. [35,36,37] In numerous studies we have reported the use of molecular simulation techniques to obtain pseudo experimental data for gas mixtures. [38,39,40,41,42,43,44] In these studies, simulated vapour-liquid equilibrium data were compared to corresponding experimental data points, and scaling laws together with additional molecular simulation results were used to calculate critical point coordinates. [39,40,42] The so obtained phase envelops can then be used to optimize binary interaction parameter values to feed EoS.…”
Section: Atomistic Molecular Simulationmentioning
confidence: 99%
“…[38,39,40,41,42,43,44] In these studies, simulated vapour-liquid equilibrium data were compared to corresponding experimental data points, and scaling laws together with additional molecular simulation results were used to calculate critical point coordinates. [39,40,42] The so obtained phase envelops can then be used to optimize binary interaction parameter values to feed EoS. [44] Moreover, it has been shown that molecular simulation results can be used to determine association scheme and association parameters of a SAFT (Statistical Associating Fluid Theory) type EoS.…”
Section: Atomistic Molecular Simulationmentioning
confidence: 99%
“…They have found that the TIP4P/2005 model corresponds to the one that best predicts on average the water behavior for all these properties. For N 2 O and N 2 , the molecular models proposed by Lachet et al [25] and Delhommelle [26] were chosen respectively. Table 6 summarizes the force field parameters used for water and for the two studied gases.…”
Section: Water Model and Gas Modelsmentioning
confidence: 99%
“…The reactive Gibbs-ensemble Monte Carlo (RxGEMC) method [18,30,31] is a combination of the reaction-ensemble (RxMC) [17][18][19] and the Gibbs-ensemble (GEMC) [32][33][34][35][36][37][38][39] methods, and it has already been used for the computation of the combined ChVLE of dimerization and combination reactions [18,30], the etherification reaction of isobutene and methanol to yield methyl-tertbutyl ether [31], and the dimerization reactions of nitrogen dioxide [40] and nitric oxide [41]. In this work, the RxGEMC method was implemented in order to compute the combined ChVLE for the hydration of ethylene to ethanol and compare the simulation predictions with those previously obtained [1] from the thermodynamic model.…”
Section: Introductionmentioning
confidence: 99%